Interventions for promoting participation in shared decision-making for children with cancer [protocol] - COYNE, IMELDA; SHEAF, GREG (My University, 2011)
This is the protocol and there is no abstract. The objectives are as follows: To examine the effects of interventions to promote shared decision-making (SDM) for children with cancer who are aged four to 18 years.
PUBLISHED
Keywords: cancer; decision-making; Childhood cancer; Smart & Sustainable Planet; Shared decision-making